Quasispecies of SARS-CoV-2 revealed by single nucleotide polymorphisms (SNPs) analysis. Issue 1 (31st December 2021) - Gao, Rongsui; Zu, Wenhong; Liu, Yang; Li, Junhua; Li, Zeyao; Wen, Yanling; Wang, Haiyan; Yuan, Jing; Cheng, Lin; Zhang, Shengyuan; Zhang, Yu; Zhang, Shuye; et al.
ABSTRACT: New SARS-CoV-2 mutants have been continuously indentified with enhanced transmission ever since its outbreak in early 2020. As an RNA virus, SARS-CoV-2 has a high mutation rate due to the low fidelity of RNA polymerase. To study the single nucleotide polymorphisms (SNPs) dynamics of SARS-CoV-2, 158 SNPs with high confidence were identified by deep meta-transcriptomic sequencing, and the most common SNP type was C > T. Analyses of intra-host population diversity revealed that intra-host quasispecies' composition varies with time during the early onset of symptoms, which implicates viral evolution during infection. Network analysis of co-occurring SNPs revealed the most abundant non-synonymous SNP 22, 638 in the S glycoprotein RBD region and 28, 144 in the ORF8 region. Furthermore, SARS-CoV-2 variations differ in an individual's respiratory tissue (nose, throat, BALF, or sputum), suggesting independent compartmentalization of SARS-CoV-2 populations in patients. The positive selection analysis of the SARS-CoV-2 genome uncovered the positive selected amino acid G251V on ORF3a. A lternative a llele f requency s pectrum (AAFS) of all variants revealed that ORF8 could bear alternate alleles with high frequency. Overall, the results show the quasispecies' profile of SARS-CoV-2 in the respiratory tract in the first two months after the outbreak.